2014
DOI: 10.2105/ajph.2014.302070
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Accuracy of Weight Loss Information Search Engine Results on the Internet

Abstract: The weight loss information that people were likely to access online was often of substandard quality because most comprehensive and quality Web sites ranked too low in search results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 31 publications
4
57
4
2
Order By: Relevance
“…While we did not perform a formal analysis of the specific content of each web page, informal review noted large numbers of advertisements and pictures of products available for sale without instruction regarding safe use and storage. Studies of web content on other topics have noted variability based upon the type of website, with worst performance on sponsored sites25 26 and commercial or news sites 24. Our study results are largely consistent with this prior work, showing better completeness among non-retail, when compared with retail pages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While we did not perform a formal analysis of the specific content of each web page, informal review noted large numbers of advertisements and pictures of products available for sale without instruction regarding safe use and storage. Studies of web content on other topics have noted variability based upon the type of website, with worst performance on sponsored sites25 26 and commercial or news sites 24. Our study results are largely consistent with this prior work, showing better completeness among non-retail, when compared with retail pages.…”
Section: Discussionsupporting
confidence: 89%
“…The average Flesch–Kincaid Reading Level of all web pages in our study was 8.0, which is similar to recently reported mean reading level of information on weight loss available on the internet24 but above published guidelines for target grade level for patient education materials 30. Flesch–Kincaid Reading Level does not fully capture all factors that contribute to reading comprehension, such as writing style, appropriate use of formatting and cultural sensitivity, but it does provide one easily standardised, measurable marker of readability.…”
Section: Discussionsupporting
confidence: 89%
“…However, our findings are consistent with one such study that concluded that most webpage content likely to be accessed by layperson Internet-users seeking weight-loss information was of suboptimal quality (11). Our findings also indicate that within the weight-loss services industry, detailed information regarding services offered is also limited.…”
Section: Discussionsupporting
confidence: 91%
“…Sin embargo, no se tiene en cuenta la calidad de las fuentes de información a la hora de extraer esta información. Así, ya se ha podido medir la calidad de sitios webs más visitados para obtener información relativa a la pérdida de peso y se ha comprobado que la calidad de los mismos generalmente suele estar por debajo de la aceptable y aunque existen sitios web de calidad admisible generalmente estos no son colocados en puestos preferentes por los algoritmos de los buscadores (29), obteniéndose resultados similares con páginas web en español relacionadas con la nutrición y los trastornos de la conducta alimentaria (30) o en general para webs relacionadas con cuestiones de salud (31). De igual modo, las app móviles más empleadas en los entrenamientos, en su mayoría, tampoco parecen estar basadas en la evidencia científica aceptada (32).…”
Section: Discussionunclassified